2006
DOI: 10.1245/aso.2006.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Combined With Intraoperative Brachytherapy in the Treatment of Retroperitoneal Sarcomas

Abstract: The scheduled combined treatment (surgery plus IOBRT) was possible to perform in 66% of RSTS cases that received surgical treatment. The complication rate was high, but we consider it acceptable because of the necessity for extensive aggressive surgical treatment in regionally advanced RSTS. EBRT seems to be an indispensable part of treatment that provides better local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Patients who received the combination of HDR-IORT and EBRT had a significant improvement in local recurrence-free survival compared with patients who received HDR-IORT alone. 50,51 Toxicity IOERT IOERT induces severe complications in up to 37% of patients; and neuropathy, hydronephrosis, gastrointestinal fistula, small bowel obstruction, and vaginal and ureteroarterial fistula are the most frequent. 17,45,49 To limit the risk of grade 3 neuropathy, the RT dose should kept below 15 Gy.…”
Section: Hdr-iortmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who received the combination of HDR-IORT and EBRT had a significant improvement in local recurrence-free survival compared with patients who received HDR-IORT alone. 50,51 Toxicity IOERT IOERT induces severe complications in up to 37% of patients; and neuropathy, hydronephrosis, gastrointestinal fistula, small bowel obstruction, and vaginal and ureteroarterial fistula are the most frequent. 17,45,49 To limit the risk of grade 3 neuropathy, the RT dose should kept below 15 Gy.…”
Section: Hdr-iortmentioning
confidence: 99%
“…10,47,50,51 Ballo et al did not use Radiation Therapy Oncology Group criteria for toxicity, but all 5 of their patients (10% at 5 years) who developed RT-related complications had received postoperative EBRT. 47 Preoperative RT Alone or in Combination With Other Forms of RT There are several theoretical advantages for preoperative RT compared with postoperative RT.…”
Section: Hdr-iortmentioning
confidence: 99%
“…The abdominal organs are positioned out of the radiation field. It also has the advantage of delivering radiation to specific areas, which carry a high risk of recurrence [36][37][38][39]. IORT is usually combined with preoperative or postoperative radiotherapy.…”
Section: Radiotherapymentioning
confidence: 99%
“…IORT is usually combined with preoperative or postoperative radiotherapy. Few retrospective studies and a prospective trial have reported favourable outcomes with IORT [20,[37][38][39], whereas a study from MD Anderson Cancer Centre (MDACC) has not found any benefit from IORT [27]. IORT is also associated with a significant amount of toxicity.…”
Section: Radiotherapymentioning
confidence: 99%
“…Promising results have been published regarding the use of intraoperative brachytherapy and intraoperative teleradiotherapy following radical excision of the sarcoma, usually in combination with perioperative teleradiotherapy (7,14,(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%